Consumer resistance against regulation: The case of health care - Peter Zweifel; Harry Telser; Stephan Vaterlaus (University of Zurich, Socioeconomic Institute, 2005)
Regulation fostering Managed Care alternatives in health insurance is spreading. This work reports on an experiment designed to measure the amounts of compensation asked by the Swiss population (in terms of reduced premiums) for Managed-Care type restrictions in the provision of health care. It finds that restrictions on the freedom of physician choice would require an average compensation of more than one-third of the premium, while generic substitution even meets with a small willingness to pay. Marked preference heterogeneity is an argument against regulation imposing uniformity of contract in Swiss social health insurance.
Keywords: L51; D61; C93; I11; I18; 330; health insurance; health care; regulation; preference measurement; discrete choice experiments; Konsumentenverhalten; Gesetzliche Krankenversicherung; Gesundheitswesen; Gesundheitsreform; Willingness to pay; Theorie; USA; Meinung; Diskrete Entscheidung